Intellectual property rights as foreign direct investments : from collision to collaboration - Vanhonnaeker, Lukas (Elgar international investment law, 2015)
What is the level of convergence between the international investment law framework and the international legal regime regulating intellectual property rights? This discerning book examines the interface between intellectual property and foreign direct investments. Taking a multi-disciplinary approach, the author scrutinizes the circumstances in which, and the extent to which, international investment law's traditional protective standards apply to intellectual property rights investments. After concluding that the TRIPS agreement has shortcomings in this respect, the author analyses intellectual property rights in the context of international investment law in light of traditional standards of protection including the protection against indirect expropriation, the National Treatment Principle, the Most-Favoured Nation clause, fair and equitable treatment, and the prohibition of performance requirements, while emphasizing the importance of transfers of technology within and to developing countries. These explorations contribute to the debates surrounding the fragmentation of international law arising from its expansion and diversification. Scholars, students and practitioners in the field of international investment law, as well as those interested in the protection of intellectual property rights at an international level, will find this book to be a useful and informative read.